Determining the Relationship Between Air Temperature and Soil Temperature at Different Depths in Jahrom Station - Saeed Shahmirzaei Jeshvaghani; Ahmad Mazidi; Yaser Mohammadi; Mostafa Safari (Nīvār)
The study of soil temperature at different depths is important for climatology (especially at the micro-scale), agriculture and industry, and affects many soil processes. The method used is descriptive-analytical and its purpose is to determine the linear and non-linear relationships of air temperature and temperature depth of 5, 10, 20, 30, 50 and 100 cm during the statistical period of 1386 to 1390 in Jahrom station... Hourly statistics of air temperature and temperature of different soil depths were obtained from Fars Meteorology and linear and non-linear relationships were extracted for each soil depth using regression method. The results showed that based on the correlation coefficient and determination coefficient, linear regression has better results than non-linear relationships and in linear relationships, the correlation coefficient between air temperature and soil depth temperature for all seasons is significant at the 99% level. The highest correlation coefficient in all seasons was usually at the depth of the soil surface, especially at a depth of 5 cm at 18:30 and the lowest correlation coefficient in all seasons was at a depth of 1 meter at 6:30. As the depth increases, the correlation coefficient and determination coefficient have a decreasing trend. The highest range of temperature fluctuations in the soil occurred at 6:30 and at depths of 5 to 20 cm, and the increase in soil temperature compared to the increase in air temperature in spring and autumn is more than in other seasons.